Cancer of Unknown Primary (CUP): genetic evidence for a novel nosological entity? A case report. Issue 7 (8th June 2020) - Benvenuti, Silvia; Milan, Melissa; Geuna, Elena; Pisacane, Alberto; Senetta, Rebecca; Gambardella, Gennaro; Stella, Giulia M; Montemurro, Filippo; Sapino, Anna; Boccaccio, Carla; Comoglio, Paolo M
Abstract: Cancer of unknown primary (CUP) is an obscure disease characterized by multiple metastases in the absence of a primary tumor. No consensus has been reached whether CUPs are simply generated from cancers that cannot be detected or whether they are the manifestation of a still unknown nosological entity. Here, we report the complete expression and genetic analysis of multiple synchronous metastases harvested at warm autopsy of a patient with CUP. The expression profiles were remarkably similar and astonishingly singular. The whole exome analysis yielded a high number of mutations present in all metastases (fully shared), additional mutations (partially shared) accumulated one after another in a series, and few private mutations were unique to each metastasis. Surprisingly, the phylogenetic trajectory linking CUP metastases was atypical, depicting a common "stream", sprouting a series of linear "brooks", at variance from the extensive branched evolution observed in metastases from most cancers of known origin. The distinctive genetic and evolutionary features depicted suggest that CUP is a novel nosological entity. Synopsis: Cancer of unknown primary (CUP) is a heterogeneous clinical syndrome characterized by metastases without primary tumor, an elusive biology and lack of effective treatments. We describe the genetic and evolutionary features of 15 synchronous and spatially distinct metastases from a CUP patient. CUP metastases were mostly genetically homogeneous, each one accruing an independent smaller mutational burden. Reconstruction of phylogenetic relationships among metastases suggested the presence of a common ancestor that linearly and rapidly accumulated mutations, and disseminated a progeny at subsequent stages of its evolution. The genomic and transcriptomic traits of CUP metastases prompted recognition of a distinct nosological entity. On the clinical ground, the unexpected genetic similarity among different CUP metastases, fosters a therapeutic strategy aimed at simultaneous eradication of the multiple lesions. Abstract : Cancer of unknown primary (CUP) is a heterogeneous clinical syndrome characterized by metastases without primary tumor, an elusive biology and lack of effective treatments. We describe the genetic and evolutionary features of 15 synchronous and spatially distinct metastases from a CUP patient.